ESP Malay learner's critical thinking skills: presenting arguments and counter arguments / Roselina Musahar, Rosita Aminullah and Noli Maishara Nordin - Musahar, Roselina; Aminullah, Rosita; Nordin, Noli Maishara (2015)
Presenting about controversial topics and issues is one of many activities conducted in English for specific purposes (ESP) classroom whereby students are required to present their arguments supported by acceptable reasons while also being able to challenge others views. Both skills, if developed we can have positive impacts on the speaker and the audience. This pilot study is aimed at investigating the relationship between the argument skills and counter argument skills among ESP Malay students. Participants of the study were UiTM Pahang diploma students in their fifth semester. The data was taken from students' speaking assessment marks for argument and counter argument skills in presenting arguments in their Introduction to Critical Thinking (BEL313) course. The data collected were analysed using SPSS version 18 for Windows to provide indicators that reflect the relationship between argument skills and counter argument skills of these students. The study revealed that there was a fair connection between the skills of argument and counter argument. The findings suggest further development of both skills is essential and beneficial where later in live they will encounter many more issues and disputes to evaluate and differentiate between what are relevant and irrelevant to them.